10-Alkenylphenothiazines; 2; Synthesis and mechanism of acidic hydrolysis of cis- and trans-10-2-phenylvinyl)phenothiazines; Chemistry of Heterocyclic Compounds; Vol. 22, iss. 10 - Anfinogenov V. A.; Napilkova O. A.; Sirotkina E. E.; Filimonov V. D. Viktor Dmitrievich; Khlebnikov A. I. Andrey Ivanovich (1986, 1986)
Title screen